PEMBERIAN STIMULASI TIC TAC SEBAGAI UPAYA OPTIMALISASI TUMBUH KEMBANG BAYI - Agi Yulia Ria Dini; Meli Deviana (Jurnal Pengabdian Masyarakat Kesehatan (JIRAH), 2022)
The success of children in achieving optimal growth and development is a determinant of the success of a nation in the future. Delay in growth and development of children can be caused by various factors including a history of low-birth-weight birth, nutritional status and stimulation. Cognitive, motor, language, social, emotional, and behavioral delays will interfere with the child's ability to learn, communicate, and interact with others which can have an impact on the quality of the child in the future. Developmental stimulation needs to be given especially by parents to children to improve aspects of child development according to their age. Tic tac stimulation is a massage therapy method with a light touch on the baby in the form of light caressing from the top of the head to the feet. The purpose of this activity is to provide knowledge and skills of mothers in providing stimulation as an optimization of child growth and development. The activity was carried out on September 3, 2022 at the Flamboyan Posyandu, Dumeling Village, Wanasari District, Brebes Regency. The instruments used are dolls as props, baby oil, cameras, and SDIDTK assessment sheets. The activity went well, at the end of the session the parents were able to provide tic tac stimulation independently to the child. The role of health workers in this case is expected to be able to provide information support about the stage of development in children and stimulation that parents can do independently at home.Keywords: Tic Tac Stimulation, Child developmentAbstrakKeberhasilan anak dalam mencapai pertumbuhan dan perkembangan yang optimal merupakan penentu keberhasilan suatu bangsa di masa yang akan datang. Keterlambatan pertumbuhan dan perkembangan anak dapat disebabkan oleh berbagai faktor diantaranya riwayat kelahiran BBLR, status gizi dan stimulasi. Keterlambatan kognitif, motorik, bahasa, sosial, emosional dan perilaku perilaku akan mengganggu kemampuan anak untuk belajar, berkomunikasi, dan berinteraksi dengan orang lain yang dapat berdampak pada kualitas anak di masa depan.  Stimulasi perkembangan perlu diberikan terutama oleh orang tua kepada anak untuk meningkatkan aspek perkembangan anak sesuai usianya. Stimulasi tic tac merupakan metode terapi pijat dengan sentuhan ringan pada bayi yang berupa belaian ringan didaerah puncak kepala sampai dengan kaki.  Tujuan kegiatan ini untuk memberikan pengetahuan dan ketrampilan ibu dalam memberikan stimulasi sebagai optimalasi tumbuh kembang anak. Kegiatan dilakukan pada 3 September 2022 di Posyandu Flamboyan Desa Dumeling Kecamatan Wanasari Kabupaten Brebes. Instrumen yang digunakan adalah boneka sebagai alat peraga, baby oil, kamera, serta lembar penilaian SDIDTK. Kegiatan berjalan baik, di akhir sesi orangtua mampu memberikan stimulasi tic tac secara mandiri ke anak. Peran tenaga Kesehatan dalam hal ini, diharapkan dapat memberikan dukungan informasi tentang tahap perkembangan pada anak dan stimulasi yang dapat dilakukan orang tua secara mandiri di rumah.Kata Kunci: Stimulasi Tic Tac; Perkembangan Anak